Perbandingan prediksi jumlah penjualan kapas menggunakan metode dekomposisi aditif dan multiplikatif - Kristuadji, Yesaya Arya Danar; Zubair, Anis (Journal of Information System and Application Development, 2024)
PT Taruna Kusuma Purinusa is a company that focuses on the beauty cotton industry with the Selection Cotton brand label. Their product sales are spread in various cities including Malang City. This study aims to determine fluctuations and predict the amount of sales of cotton PT Taruna Kusuma Purinusa Malang and simultaneously compare the two methods of Decomposition, namely Multiplicative Decomposition and Additive Decomposition. The data is secondary on cotton sales from January 2019 to May 2023. The research procedure begins by analyzing the components of the decomposition, namely the trend (ð‘‡), seasonal (ð‘†), cyclical (ð¶) and random (ð¼) components, then multiplying the value of these components. The prediction results show that cotton sales from June to December 2023 are as follows: 1,759,864 in June, 1,691,855 in July, 1,744,614 in August, 1,720,060 in September, 1,746,516 in October, 1,850,913 in November, and 1,893,669 in December. In addition, the proper forecasting method used in the Cotton Sales data at PT Taruna Kusuma Purnisua Malang is the additive decomposition method.